Pengaruh Ekstrak Bengkuang (Pachyrhizus erosus) terhadap Kadar Trigliserida Darah Tikus Putih (Rattus norvegicus) yang Diberi Diet Tinggi Lemak - Fuad, Himmatul; Suhanantyo, .; Setyawan, Novan Adi (Nexus Biomedika, 2014)
Background: Yam Bean contains flavonoids, isoflavones, phenols, alkaloid, ascorbic acid and saponins which have the effect of antihyperlipidemia. This study aimed to determine the effect of Yam Bean (Pachyrhizus erosus) extract on blood triglyceride level of rats (Rattus norvegicus) with a high fat diet. Methods: This research was a true experimental laboratory research using the post test only with control group design. This research subjects were 30 male white rats, Sprague Dawley strain, 2 months old, and about 137-238 gram of their weight. The subjects were divided by random into 6 groups. The whole groups were adapted for 7 days. After a week, all groups except normal control group, were administered high fat diet 2 ml/200 gram BW/day for 21 days. In addition, the positive control group were also administerd 0.18 mg/200 g BW/day of simvastatin, while the negative control groups were administered 2 ml/200 g BW/day of distilled water. The first, second and third treatment groups were consecutively administered 70 mg, 140 mg and 210 mg/200 g BW/day ofÂ  Yam Bean extracts. In the 22th day, the blood samples of the subjects were taken from pre-orbital plexus to assess their triglyceride levels. The data were analyzed using One-way ANOVA test and Least Significance Difference test (LSD). Results: The One-way ANOVA test showed a significant difference in blood triglyceride level among six groups (p = 0.001). Whereas, Post Hoc test showed a significant difference among all groups, except the third treatment group which had no significant difference (p=0.768) to the positive control group. Conclusions: Yam Bean (Pachyrhizus erosus) extract significantly reduced blood triglyceride levels of rats. Keywords: Yam Bean (Pachyrhizus erosus) extract, triglyceride levels, white rats.Â